The Prevalence of blaNDM-1 in Clinical Isolates of Carbapenem-resistant Pseudomonas Aeruginosa: A Systematic Review - Bea Jorelli U. Fernando; Ma. Oryza B. Antonio; Ken Matthew A. De Guzman; Jan Carlo Y. Gatbonton; Sunshine T. Vendivil; Raphael Enrique G. Tiongco; Sherill D. Tesalona (Ital Publication, 2021)
Background: Pseudomonas aeruginosa (P. aeruginosa) is a gram negative bacteria that is known to cause nosocomial infections. Carbapenem is used to treat the damage caused by P. aeruginosa, however it is becoming resistant to carbapenems because of the production of β-lactamases. The objectives of the study were to systematically review the prevalence of blaNDM-1 in carbapenem-resistant Pseudomonas aeruginosa (CRPA) and to review and analyze the clinical sources as well as the antibiotic resistance profile of CRPA carrying blaNDM-1. Methods: The researchers systematically searched PubMed, ScienceDirect, and Google Scholar. Studies that met the inclusion criteria were included in the review. In assessing the methodological quality of the included studies, the JBI Critical Appraisal Checklist for Studies Reporting Prevalence Data and the JBI Critical Appraisal Checklist for Case Reports were used. Results: A total of nine studies were included in which eight were cross-sectional studies and one was a case report. The highest prevalence rate reported was 54.55% in blaNDM-1 positive CRPA isolates among the cross-sectional studies. The three most frequent sources of clinical isolates of CRPA carrying blaNDM-1 include urine, wound discharge, and tissue, among the included studies. Lastly, this review showed that among the included studies, CRPA isolates carrying blaNDM-1 were most resistant to ceftazidime and gentamicin. Conclusions: There is varying prevalence of blaNDM-1 in CRPA in different countries. Urine, wound discharge, and tissue specimens being the most frequent sources of CRPA isolates carrying blaNDM-1 poses a challenge that must be given attention by the  infection control committee, thus the need for proper handling and processing of clinical specimens. Resistance to ceftazidime and gentamicin among the CRPA isolates carrying blaNDM-1highlights the growing challenge of successfully treating infections caused by this bacteria. This challenge reminds us of the importance and purpose of antibiotic stewardship that emphasizes the improvement of proper antibiotic prescription by the physicians and proper antibiotic use by the patients that can help in preventing harm and antibiotic resistance.   Doi: 10.28991/SciMedJ-2021-0304-9 Full Text: PDF